New high intensity fibreoptic phototherapy devices in healthy newborns: a single pad wrapped around the neonate body in comparison with a double pad device - R. Luciano; G. Mancini; F. Cota; A. Romano; V. Purcaro; F. Lerro; M. Corsello; G. Vento (BMC, 2019)
Abstract Background Fibreoptic Phototherapy (FPT) allows to lower total serum bilirubin (TSB) levels in healthy neonates maintained in rooming-in with their mothers. The 2004 Cochrane review showed that, differently from preterm neonates, FPT was not as effective as traditional phototherapy in term neonates (TN), unless the simultaneous utilization of two FPT devices. Aim of this study was to compare the efficacy of two FPT devices, both equipped with a single light-emitting diode (LED): the first one has a single large pad wrapped around the infant body (Bilisoft, GE Health Care) (device A), the second one is a double-pad phototherapy device (BiliCocoon, CremascolieIris) (device B). Methods We studied 172 healthy neonates with non-hemolytic hyperbilirubinaemia: 57 TN and 57 late preterm neonates (LPN) treated with device A (Group 1); 47 TN and 11 LPN treated with device B (Group 2). We evaluated the differences between groups by the Student's t-test for continuous variables and by chi square test for categorical data. A two tailed p < 0.05 was considered significant. Results There were no differences in term of duration of FPT, TSB hourly reduction, percentage of TSB reduction after FPT, TSB maximum rebound, percentage of TSB increase after FPT discontinuation and number of after-discharge checks. Two neonates treated with device B showed no decrease in TSB values during FPT. Seven infants treated with device B experienced hyperpyrexia. Conclusions The two LED FPT devices were both effective in lowering TSB either in TN or LPN. Device A was effective in all treated neonates without negative side effects during treatment; device B was effective in all but 2 infants and 12% of the neonates in the same group experienced hyperpyrexia. According to our results, the single big pad wrapped around the infant body has the same efficacy as a double FPT device in TN and LPN.